PERANAN INTERNATIONAL ATOMIC ENERGY AGENCY (IAEA) MELALUI THE INTERNATIONAL FACT FINDING EXPERT MISSION OF THE FUKUSHIMA DALAM PENANGANAN KERUSAKAN REAKTOR NUKLIR DI JEPANG PASCA TSUNAMI 11 MARET 2011 - Chrisnanta Amijaya (Global Political Studies Journal, 2018)
Utilization of nuclear energy in many countries is a particular concern for international. This not talk only have a positive impact, but also have a negative impact. The damage of Fukushima Nuclear Power Plant, Japan is one example of the negative impacts of the use of nuclear energy. March, 11th 2011, 9.2 magnitude earthquake followed by tsunami has destroyed a nuclear power plant that located on the edge of Japan’s sea. This problem get a special concern for International Atomic Energy Agency (IAEA) because it involves the safety and security of utilizing nuclear energy. The approach of this research is a qualitative; the method is descriptive analyzing technique. Data were collected through library research, website research, and interview. Those data were analyzed by theory approach based on International Relation sciences. This research use main theory is role of International Organization theory, such as international organizations as an instrument, as an arena, and as an actor to shows that international organizations, in this case IAEA, show its role in the nuclear